A cell-free system for functional centromere and kinetochore assembly - Guse, Annika; Fuller, Colin J.; Straight, Aaron F. (Nature protocols, 2012)
This protocol describes a cell-free system for studying vertebrate centromere and kinetochore formation. We reconstitute tandem arrays of centromere protein A (CENP-A) nucleosomes as a substrate for centromere and kinetochore assembly. These chromatin substrates are immobilized on magnetic beads and then incubated in Xenopus egg extracts that provide a source for centromere and kinetochore proteins and that can be cycled between mitotic and interphase cell cycle states. This cell-free system lends itself to use in protein immunodepletion, complementation and drug inhibition as a tool to perturb centromere and kinetochore assembly, cytoskeletal dynamics, DNA modification and protein post-translational modification. This system provides a distinct advantage over cell-based investigations in which perturbing centromere and kinetochore function often results in lethality. After incubation in egg extract, reconstituted CENP-A chromatin specifically assembles centromere and kinetochore proteins, which locally stabilize microtubules and, on microtubule depolymerization with nocodazole, activate the mitotic checkpoint. A typical experiment takes 3 d.